PENGARUH MEKANISME CORPORATE GOVERNANCE, RASIO KECUKUPAN MODAL, DAN LDR TERHADAP KINERJA KEUANGAN PERBANKAN - Hendrian Perdana; Fajri Adrianto (Menara Ilmu, 2020)
This study aims to analyze the Effect of the Corporate Governance Mechanism, Capital Adequacy Ratio, and Intermediary Function Indicators (LDR) on Banking Financial Performance. The population in this study is the banking sub-sector companies on the Indonesia Stock Exchange Period 2014-2018. The sampling method used was purposive sampling using panel data regression analysis with the help of Eviews 10. The results of this study indicate that the Corporate Governance mechanism in this study consisted of the number of members of the audit committee, the composition of the board of commissioners, and public share ownership had no significant effect on financial performance (Return On Assets), as well as the capital adequacy ratio (Capital Adequacy Ratio) does not significantly influence the financial performance of banks. While the Banking Intermediation Function Indicator (Loan to Deposits Ratio) has a significant effect on financial performance (Return on Assets). Keywords: Corporate Governance, Return on Assets, Audit Committee Members, Board of Commissioners Composition, Public Share Ownership, Capital Adequacy Ratio, Loan to Deposit Ratio